A pest of significant economic importance detected for the first time in Mozambique: Bactrocera invadens Drew, Tsuruta & White (Diptera: Tephritidae: Dacinae) (Bollettino di zoologia agraria e bachicoltura, 2024)
Bactrocera invadens Drew, Tsuruta & White (Diptera: Tepbritidae: Dacinae) is detected for the first time in Mozambique, Niassa Province, Cuamba. It is an important pest of tropical fruits, such as guava, mango, citrus, papaya, tomato, etc. The arrival to Mozambique of B. invadens can have considerable implications for agriculture in Mozambique and its Plant Pest Quarantine and export programmes.
Keywords: Bactrocera invadens; Tephritidae; Mozambique; Niassa